Effect of Dimethyl Borate Composition on the Properties of Boron Doped ZnO Films Synthesized by Hydrothermal Method - Roza, L.; Rahman, M.Y.A. (Program Studi Pendidikan Fisika UHAMKA, 2016)
In this study, boron doped ZnO nanostructure films were synthesized by hydrothermal method utilizing various compositions of dimethyl borate as source of dopant. The effect of composition of dimethyl borate on the morphology, optical properties and structure of the films was investigated by field emission scanning electron microscopy (FESEM), UV-Vis spectrofotometer and x-ray diffraction (XRD), respectively. The FESEM results indicate that the composition of dimethyl borate significantly modify the diameter of B-doped ZnO nanorods. It is also observed from the analysis of XRD result that the crystalline quality of the films decreases with dimethyl borate composition. The band gap of the films increases with dimethyl borate composition. The room temperature spectra photoluminescence shows ultra-violet (UV) and visible emission. The 10 wt. % sample possesses the highest peak intensity at UV emission. Meanwhile, the 1.0 wt. % sample shows the lowest peak intensity at visible emission. It was expected that the 1.0 wt. % sample suppresses the existence of native defect such as singly ionized oxygen vacancies, zinc interstitials or their complexes in B-doped ZnO nanorods.